TIKTOK FOR LEARNING ENGLISH: ITS AFFORDANCE AND CHALLENGES - Paras Lahiria Iklim; Andi Rahmawati Syarif; Faridawati Faridawati (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This research aimed to figure out students’ points of view toward speaking skill improvement and its challenges by utilizing TikTok content. This research applied descriptive qualitative research. To collect the data, the researcher utilized an open-ended questionnaire and interview, and involved all active undergraduate students majoring in English Education at Muhammadiyah University of Kendari. This research applied the data analysis technique by Miles et al. (2014). This research displayed that there were several reasons - why students utilized TikTok for their speaking skill improvement, they are affordability, attractiveness, algortihm dependency, beneficial outcome, and content creator. First, students enjoyed improving their speaking skills through TikTok due to its easiness of finding the desired content. Furthermore, TikTok provides English educational content in unique and fun way for students to consume. As a consequence students experienced an enjoyable environment while learning. It is recommended that students’ speaking skill improvement be compared through various social media platforms. Second, the researcher recommends future researchers follow up this research finding by revealing students’ actual improvement. Third, the researcher recommends figuring out other skills improvement through this platform